1. RELATIONSHIP BETWEEN QUALITY OF LIFE AND CLINICAL FEATURES OF CIRCULAR PATIENTS RECEIVING INPATIENT TREATMENT AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Analysis of the relationship between quality of life and some paraclinical clinical characteristics of cirrhosis patients hospitalized at Bach Mai hospital, 2023 - 2024.Research subjects and methods: Cross-sectional descriptive study, conducted at the Center for Tropical Diseases and the Hepatobiliary Digestive Center of Bach Mai Hospital from March 2023 to March 2024. The study included 216 people with cirrhosis who met the selection criteria. The study used the Chronic Liver Disease Questionarie (CLDQ) scale to measure QoL.Results: The majority of patients had average quality of life (QoL) and good quality of life, 75% and 25%, respectively. No one has low QoL. Clinical factors related to reduced quality of life include: ascites (OR=3.04, p
Keywords: Quality of life, cirrhosis, Chronic Liver Disease Questionnaire (CLDQ).